Program does not equal program: Constraint programming and its relationship to mathematical programming - Lustig, Irvin J; Jean-Francois Puget (Interfaces (Providence), 2001)
Arising from research in the computer science community, constraint programming is a fairly new technique for solving optimization problems. For those familiar with mathematical programming, a number of language barriers make it difficult to understand the concepts of constraint programming. In this short tutorial, an explanation is given of how it relates to familiar mathematical programming concepts and how constraint programming and mathematical programming technologies are complimentary. A minimal background in linear and integer programming is assumed.